E-records management system for mobile work in UiTM / Saiful Farik Mat Yatin ... [et al.] - Mat Yatin, Saiful Farik; Ahmad, Mohd Nazir; Samsudin, Ahmad Zam Hariro; Hussin, Nurussobah (Faculty of Information Management, 2022)
Record management is one of the key concerns in the world of mobile work, and mobile workers must overcome a number of obstacles to ensure that record management is carried out as effectively as possible. In order to do their daily activities and ensure that records can be managed properly and that there is no issue in relation to record management mobile workers need to discover new knowledge linked to the abilities of using ICT and technological devices. This study tries to pinpoint organisational record management motivational factors, challenges faced by mobile workers, and technical issues they encounter.